The Promise of AI in Detection, Diagnosis, and Epidemiology for Combating COVID-19: Beyond the Hype - Abdulkareem, Musa; Petersen, Steffen E. (Frontiers in Artificial Intelligence, 2021)
COVID-19 has created enormous suffering, affecting lives and causing deaths. The ease with which this type of coronavirus can spread has exposed weaknesses of many healthcare systems around the world. Since its emergence, many governments, research communities, commercial enterprises and other institutions and stakeholders around the world have been fighting in various ways to curb the spread of the disease. Science and technology have helped in the implementation of policies of many governments that are directed towards mitigating the impacts of the pandemic and in diagnosing and providing care for the disease. Recent technological tools, artificial intelligence (AI) tools in particular, have also been explored to track the spread of the coronavirus, identify patients with high mortality risk and diagnose patients for the disease. In this paper, areas where AI techniques are being used in the detection, diagnosis and epidemiological predictions, forecasting and social control for combating COVID-19 are discussed, highlighting areas of successful applications and underscoring issues that need to be addressed to achieve significant progress in battling COVID-19 and future pandemics. AI has huge potential in the battle against the COVID-19 pandemic but successful practical deployments of these AI-based tools have so far been limited. The COVID-19 pandemic has highlighted the importance of multidisciplinary research collaborations that will only accelerate the translation of AI research into practical and useful solutions in healthcare.